Antibacterial activity of bioactive compounds extracted from red kidney bean (Phaseolus vulgaris L.) seeds against multidrug-resistant Enterobacterales - Ebrahim, Azhar E.; Abd El-Aziz, Norhan K.; Elariny, Eman Y. T.; Shindia, Ahmed; Osman, Ali; Hozzein, Wael N.; Alkhalifah, Dalal Hussien M.; El-Hossary, Dalia (Frontiers in Microbiology, 2022)
In the present study, biologically active compounds such as phenolic-rich extract (PRE), 7S (vicilin), and 11S (legumin) globulins from red kidney bean (Phaseolus vulgaris L.) seeds were prepared and evaluated as antibacterial agents against multidrug-resistant (MDR) Enterobacterales isolated from animal and human sources. The overall occurrence rate of Enterobacterales was 43.6%, which significantly differed between animal (38.75%) and human (56.67%) sources. Antimicrobial susceptibility testing revealed that Enterobacterales isolates originated from animal and human sources were highly resistant to amoxicillin-clavulanate (100%), followed by ampicillin (75.44%), erythromycin (71.93%), cefoxitin (70.18%), amoxicillin (66.66%), ceftriaxone (64.91%) and trimethoprim/sulfamethoxazole (56.14). Worthy of note, 97.92% of Enterobacterales isolates were categorized as MDR. The total phenolic content (TPC) and total flavonoid content (TFC) of PRE have recorded 53±2 mg GAE g-1 extract and 26 ±1 mg QE g-1 extract, respectively. The major phenolic and flavonoid compounds are catechol (17.63 µg/mL) and hesperidin (11.37 µg/mL), respectively. The molecular mass of 7S and 11S globulins were demonstrated by sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE), and the data revealed that red kidney bean protein isolate (KPI) consists of two major fractions: 7S and 11S globulins. The antibacterial activity of Phaseolus vulgaris bioactive compounds against Enterobacterales was investigated here for the first time. The protein component (MIC = 0.125 - 2 µg /mL; 53.85%) and its 7S and 11S globulin subunits (0.5 – 2 µg /mL; 30.77% each) were the most potent extracts, whereas the methanolic extract was the least effective one (2 µg /mL; 15.38%). These results exhibited the potential of protein bioactive compounds as a promising alternative for improving future dosing strategies to treat Enterobacterales originating from animal and human sources.